Hg2+ incorporation in Andean Patagonian ultraoligotrophic lakes: insights into the role of pelagic protists - Dieguez, Maria del Carmen (2022)
In ultraoligotrophic lakes of Andean Patagonia, microbial assemblages at the base of pelagicfood webs bear high THg concentrations compared to planktonic consumers. In this study, we evaluate experimentally the passive and active (trophic) uptake of Hg2+ using 197Hg2+ to trace Hg incorporation in picoplankton (autotrophic and heterotrophic bacteria), in the photoautotrophic phytoflagellate, Gymnodinium paradoxum, and in the mixotrophic ciliates, Stentor araucanus and Ophrydium naumanni. The studied protists were found to incorporate substantial amounts of dissolved Hg2+; however, their potential for Hg transference to higher trophic levels depends on their degree of Hg internalization (citoplasmatic Hg), which varied widely among species.